163 Peak-Infection Application of Increased SID Lysine:ME Diets Does Not Improve Disease Challenge Growth Performance. (12th April 2022) - Miller, Kayla A; Mendoza, Omarh; Shull, Caleb M; Baumann, Tyler; Gabler, Nicholas K
Abstract: Increasing dietary SID Lys:ME augments growth performance of Porcine Reproductive and Respiratory Syndrome virus (PRRSV) challenged pigs when diets with greater SID Lys concentrations are in place at time of infection. Our objective was to evaluate the delayed implementation of increased SID Lys:ME diets post PRRSV challenge on pig performance. 491 grower pigs (45.8 ± 7.4 kg BW) were assigned to 1 of 3 dietary strategies (n = 16 pens/treatment, 10-11 pigs/pen). All pigs received a common diet from day post inoculation (dpi) -14 to dpi 21 (P1), that met SID Lys:ME recommendations. From dpi 21 to 77 (market body weight), dietary treatments were implemented in 2 phases (P2 and P3). The 2 dietary treatments were 2.23 g/Mcal (100%), 2.56 g/Mcal (115%), 2.90 g/Mcal (130%) in P2; and 1.92 g/Mcal (100%), 2.21 g/Mcal (115%), 2.49 g/Mcal (130%) in P3. On dpi 0, all pigs were inoculated with PRRSV. Pig BW, feed disappearance and feed efficiency were determined in each phase. Data were analyzed with pen as the experimental unit in a complete randomized design. During P1, ADG, ADFI, or G:F did not differ ( P < 0.05). In P2 and P3, ADG, ADFI, or G:F did not differ between the 100%, 115% and 130% treatments ( P > 0.10). Overall, ADG (0.90, 0.90 and 0.92 kg/d, P = 0.44) and ADFI (2.61, 2.57 and 2.57 kg/d, P = 0.48) did not differ between the 100%, 115% and 130% treatments, respectively. However, overall G:F was significantly higher for the 130% compared with the 100% and 115% treatments (0.36 versus 0.34 and 0.35, respectively; P = 0.021). Mortality was similar across treatments ( P = 0.717). In conclusion, delayed feeding of diets with increased SID Lys:ME post infection was not beneficial to pig performance indicating this diet strategy needs to be in place near time of disease challenge.